Sociedades en construcción : la Nueva Galicia según las visitas de oidores, 1606-1616 - Berthe, Jean-Pierre.; Jimenez Pelayo, Agueda; Calvo, Thomas (Guadalajara, Jalisco, México : Universidad de Guadalajara, Coordinación Editorial ; México, D.F. : Centre Français d'Études Mexicaines et Centraméricaines, 2000)
Colonial reports of three representatives of the Spanish crown in Guadalajara, charged with investigating and resolving problems between colonial authorities and indigenous groups in the areas of government, crime, agriculture, mining and customs.
Includes bibliographical references (p. [357]-360) and indexes.
Mode of access: Internet.
Keywords: Indigenous peoples -- Mexico -- Nueva Galicia -- Government relations -- Sources; Indians of Mexico -- Mexico -- Nueva Galicia -- Government relations -- Sources; Jalisco (Mexico) -- History -- Sources; Nueva Galicia -- History -- Sources